KEJAYAAN PENGLIBATAN GOLONGAN WANITAKOMUNITI ORANG ASLI SUKU KAUM MAH MERI DI DALAM BIDANG KEUSAHAWANAN - Mohamad Asri, Mohamad Anis; Roddin, Rohayu; Ahmad Hariri, Tun Ili Ayuni (Online Journal for TVET Practitioners, 2018)
This paper is a concept paper aims to discuss the success of the involvement of the Mah Meriâ€™s women in entrepreneurship. The problem of poverty is a major problem that faced by Aboriginal communities since for a long time ago. In addition, other issues which are barriers to achieving their development is the attitude of not openness to change. The role of women in the process of achieving the successful development of a society seen as a holistic solution. The women viewed as people who can contribute to the progress and development of society and the state. Experience from self-serve economy practiced by them, Aboriginal communities are seen as the best communities to bring that experience to a favorable change for them. Entrepreneurship is a strategy that is very close to the women of the Aboriginal communities because of their experience that they have. Hence, these entrepreneurship areas need to be developed in the women as well as helping men to carry out entrepreneurial activities. This process is supported by the provision of opportunities provided by the government in enhancing their capabilities. The opportunities provided such as courses and training have been used as a source of entrepreneurial education to them in the pursuit of entrepreneurial activity. In conclusion, this paper is important for researchers to provide exposure of the women in a group of Orang Asli community who have ability and openness to success. They take the opportunities that have been provided as a beneficial resource for them to getting profitable changes. It is hoped that this paper will serve as a benchmark for others women of the Indigenous Orang Asli communities to join with Mah Meri’s women in achieving successful in entrepreneurship and at the same time can elevate the value of their gender in community.